On the Design of Differential Difference Transconductance Amplifier (DDTA) and Its Applications - Channumsin, Orapin; Yaruan, Panurut; Tangsrirat, Worapong (My University, 2026)
This paper presents the design and implementation of a novel active building block termed the Differential Difference Transconductance Amplifier (DDTA). The proposed DDTA integrates the characteristics of the Differential Difference Amplifier (DDA) and the Transconductance Amplifier (TA) to enhance flexibility in analog signal processing. It comprises three TA stages—two forming a DDA structure and one functioning as a TA—allowing independent electronic tuning of transconductance gain (gm). The DDTA features a simple architecture, wide input capability, extremely high input impedance, and high output resistance at both intermediate and output current terminals, enabling accurate current-mode signal processing with minimal loading effects. To demonstrate its versatility, a voltage-mode universal biquadratic filter and dual-mode quadrature oscillator, both based on a single DDTA and utilizing only two capacitors, have been designed and simulated. PSPICE simulation results confirm wide linear voltage-to-current conversion, wideband transconductance performance, and robust impedance characteristics, all in excellent agreement with theoretical predictions. These features validate the effectiveness and practicability of the proposed approach for modern analog circuit designs.
Keywords: analog Integrated Circuit (IC); Differential Difference Transconductance Amplifier (DDTA); electronic tunability; multifunction filter; transconductance amplifier